Relasi Agama Kristen dan Lima Agama Lain di Indonesia: Perspektif Trinitas - Grace Son Nassa (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2022)
The relationship between Christianity and other religions is a necessity today. In such conditions, Christians are required to have good relations and at the same time adapt to the situations and conditions created by these relationships, as well as how to do theology in them. This paper aims to provide a relationship model for Christians in relating to people from five religions in Indonesia through the perspective of the Trinity. Based on library research, the method used is content analysis. The author sorts out the writings that discuss the Trinity, then takes and analyzes important principles from it regarding good relations, and then uses them in the relationship between Christianity and five other religions in Indonesia. Christians must maintain their specificity as a religion justified in Christ, but remain humble and not very exclusive in their relations with other religions, open minds but remain critical of both Christianity itself and other religions.